The marriage method [large type] - Matthews, Mimi (Matthews, Mimi. Crinoline academy, 2026)
"Well removed from London's more curious eyes, the Benevolent Academy for the Betterment of Young Ladies strives toward one clandestine goal: to distract, disrupt, and discredit men in power who would seek to harm the advancement of women--by appropriate means, of course. When intrepid newspaper editor Miles Quincy starts to question the school's intentions, the Academy appoints Penelope "Nell" Trewlove, one of their brightest graduates, to put this nuisance to rest. An easy enough mission, she supposes. Or it would be, if Miles wasn't so fascinating--too fascinating to resist--and if Nell's visit to London didn't perfectly coincide with the murder of one of Miles's reporters. When the inexorable claws of fate trap Nell and Miles in a compromising situation, they agree to an arrangement that will save their reputations while enabling them to investigate the story that led to a man's death, as well as the surprising chemistry between them . . ."--